Trabajo no remunerado en las mujeres graduadas y egresadas de la carrera de Sociología 2021-2022. - Peña Pico, Gina Stefania (2024)
El The present work aims to precisely understand how female student domestic work is currently perceived, whether it is considered a contribution to the economy or rather seen as an obligation for women. For many years, women have been regarded as homemakers, given the activities they perform within the household (such as washing, ironing, cooking, etc.), considered reproductive rather than productive. The main objective is to determine the impact of unpaid work on the living conditions of sociology graduates and students through field research conducted between November-March 2021 and November-March 2022. Bourdieu mentions that the naturalization of the social world corresponds to a form of domination based on symbolic violence, known as passing down customs to descendants and thus creating a social habitus. This research will employ a quantitative methodology and surveys as a data collection technique to understand the situation of sociology graduates and students. The investigation involves an extensive literature review that better problematizes the conditions of unpaid work in the home, particularly focusing on women, especially female university students in the sociology program at Bolivar State University in Guaranda. This information is valuable for understanding and discussing the relevance of current gender roles in our society. Keywords: Female student domestic work, unpaid work, gender roles, symbolic violence, living conditions, sociology.